Urban Economic Empowerment Strategy Based on a Business Model Canvas: Case Study of the ZCHICKEN Empowerment Program by BAZNAS - Sayyid Ahmad, Muhammad Malik; Yusnita, Titien; Arijulmanan, Arijulmanan (Review of Islamic Economics and Finance, 2024)
AbstractPurpose – This research aims to analyze sharia economic development strategies, the concept of zakat, and optimization using the Business Model Canvas approach in the ZCHICKEN program carried out by BAZNAS to increase the income of small traders.Methodology - This type of research is descriptive qualitative using analytical tools in the form of the Business Model Canvas for Social Enterprise and SWOT analysis to find relevant strategies. Findings - The results of this research are that the sharia economic development strategy carried out by BAZNAS in the ZCHICKEN program in Jakarta to increase the income of small traders has succeeded in empowering mustahik by providing opportunities for economic empowerment in the culinary sector through the concept of fried chicken franchises, namely some have reached the nisab, had kifayah, or above the poverty line. The concept of zakat in the ZCHICKEN program is zakatnomics which focuses on the economic aspects of zakat including faith, productivity, economic justice, and BAZNAS. The results of the Business Model Canvas identification in the ZCHICKEN BAZNAS program have effectively utilized productive zakat funds by providing capital assistance and training so as to have a positive impact on the welfare of mustahik to build family economic resilience by prioritizing strengths and opportunities. Keywords: ZCHICKEN BAZNAS Zakat Concept; Urban Economic Empowerment; Business Model Canvas; SWOT Analysis.